Polymerization and Rheological Behavior of the Thermoresponsive Gelcasting System Based on N‐isopropylacrylamide. Issue 5 (1st July 2016) - Wang, Xiaofeng; Peng, Chaoqun; Wang, Richu; Zhang, Dou; Zeng, Jing; Feng, Yan
Abstract : Recently, we developed an efficient method for rapid drying and improving relative density of the gelcast green body. In this work, polymerization and rheological behavior of the thermoresponsive gelcasting system based on N‐ isopropylacrylamide were investigated. To initiate reaction of the system with 4 mL/L of catalyst, 0.25–0.5 mg/mL of initiator is considered optimal in the optimized temperature range 15–20°C. Suspensions with 40–55 vol.% solid loading still show shear‐thinning behavior, which is favorable for mixing, degassing, and casting. The final storage moduli of consolidated suspensions are approximately 10 4 Pa, which is sufficiently high for gelcast green bodies.